Regime shift on the roof of the world: Alpine meadows converting to shrublands in the southern Himalayas - Brandt, Jodi S.; Haynes, Michelle A.; Kuemmerle, Tobias; Waller, Donald M.; Radeloff, Volker C. (Biological conservation, 2013)
► We reconstructed alpine change from 1950 to 2009 in northwest Yunnan, China. ► From 1990 to 2009, 39% of the alpine meadows converted to woody shrubs. ► Patterns of change suggest that a catastrophic regime shift is occurring. ► Shrub encroachment was driven by climate change, fire restrictions, and grazing. ► This regime shift threatens both endemic meadow biodiversity and local livelihoods. Worldwide, changing climates and land use practices are escalating woody-plants encroachment into grasslands, reducing biodiversity and altering ecosystem functions. The loss of alpine grasslands is a major conservation concern as they harbor many rare and endemic species. Alpine meadows in Northwest Yunnan, China, represent a global biodiversity hotspot with high species richness, beta diversity, and endemism. Shrubs have expanded greatly in the region and threaten alpine meadow biodiversity. To measure rates of meadow loss due to shrub encroachment and identify its mechanisms, we reconstructed alpine land cover, climate, and land use change from 1950 to 2009 across Northwest Yunnan using satellite data, ground surveys, and interviews. Between 1990 and 2009, at least 39% of the alpine meadows converted to woody shrubs. The patterns of change suggest that a regime shift is occurring. Despite multiple perturbations to the climate and land use systems starting in the 1950s, alpine meadows remained resilient to shrub expansion until the late 1980s. Shrublands rapidly expanded then due to feedback mechanisms involving climate, woody cover, and grazing. Fire may no longer be an effective tool for controlling shrub expansion. This regime shift threatens both endemic meadow biodiversity and local livelihoods. More generally, these trends serve as a warning sign for the greater Himalayan region where similar vegetation changes could greatly affect livelihoods, hydrology, and climate.